Dilema Sewa Rahim dalam Islam : Antara Keinginan Memiliki Anak dan Batasan Syariat - Nashwa Rifda Agustina; Anita Zulfa; Machda Putri Puspaningtyas (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Advances in reproductive technology are proof that this world was not created by any other chance. With the emergence of reproductive technology updates such as womb rental, many couples choose this shortcut, without considering the established sharia. In Indonesia, this practice is also prohibited because it is exploitation and lowers the dignity of a woman. There are several alternative ways to solve this problem by adopting a child or medical procedures such as in vitro fertilization (IVF). Even though alternative ways have been found, Muslims must still involve mature religious considerations and guidance from trusted scholars.